2008
DOI: 10.3928/15428877-20080301-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Optical Coherence Tomography and Scanning Laser Polarimetry in Glaucoma, Ocular Hypertension, and Suspected Glaucoma

Abstract: RNFL thickness measurements obtained with OCT and SLP-VCC correlate well only in eyes with more advanced glaucomatous damage. The nerve fiber indicator parameter derived by SLP correlated best with mean deviation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
1
0
1
Order By: Relevance
“…The NFI was described as a very sensitive index of glaucomatous damage with the highest area under the curve (AUC), in a few studies. [1820] In our study the greatest change was noted in the NFI, postoperatively. For patients with documented advanced or moderate glaucoma, post cataract surgery, the apparent decrease in the NFI value would give a false indication of clinical improvement.…”
Section: Discussionsupporting
confidence: 46%
“…The NFI was described as a very sensitive index of glaucomatous damage with the highest area under the curve (AUC), in a few studies. [1820] In our study the greatest change was noted in the NFI, postoperatively. For patients with documented advanced or moderate glaucoma, post cataract surgery, the apparent decrease in the NFI value would give a false indication of clinical improvement.…”
Section: Discussionsupporting
confidence: 46%
“…In a previous study, Zangwill and colleagues14 compared RNFL thickness measured by OCT with stereophotography of the optic disk and VF in normal eyes, patients with ocular hypertension, patients with suspected glaucoma, and glaucomatous patients and reported that average RNFL thickness seems to be a useful quantitative value for glaucoma diagnosis and follow-up, as an important correlation of 35%–45% between mean deviation of Humphrey achromatic perimetry and RNFL thickness was found. According to the results of our study, average RNFL thickness does not have a strong correlation with the indices of the VF, except in patients with progressive structural alterations (P < 1%) detected with OCT.…”
Section: Discussionmentioning
confidence: 99%
“…Το OCT προσφέρει τη δυνατότητα ποσοτικής και ποιοτικής ανάλυσης του πάχους των νευρικών ινών . Μια μελέτη που έγινε από τον Halkiadakis I et al(391) στην οποία μετρήθηκε το πάχος των νευρικών ινών με OCT και με Scanning Laser Polarimetry (SLP) σε φυσιολογικά άτομα, ασθενείς ύποπτους για γλαύκωμα και με γλαυκωματικές αλλοιώσεις έδειξε πως το μέσο πάχος των νευρικών ινών σχετίζεται καλά μόνο για τους ασθενείς με προχωρημένες γλαυκωματικές αλλοιώσεις. Από τη μελέτη μας προέκυψε μια μέτρια συσχέτιση στατιστικά σημαντική μεταξύ του μέσου πάχους των νευρικών περιθηλαίων ινών και των γενικών δεικτών του οπτικού πεδίου για το σύνολο των ατόμων που έλαβαν μέρος και που άνηκαν σε διάφορα στάδια της εξέλιξης του γλαυκώματος.…”
unclassified